Direct, digital & data-driven marketing - Spiller, Lisa (Thousand Oaks : SAGE, 2020)
'In this latest edition of her classic text, Lisa Spiller takes an insightful, in-depth look at contemporary marketing concepts, tactics, and techniques and the dynamic innovations that continue to drive and shape this multi-faceted, multi-dimensional field'--
Part 1: Build, Develop, and Measure Direct Marketing Strategies Chapter 1: Processes and Applications of Direct Marketing Chapter 2: Database Marketing and Customer Relationship Management Chapter 3: Lists and Market Segments Chapter 4: Marketing Analytics: Testing and Measurement Part 2: Create and Place Direct Marketing Campaigns Chapter 5: The Offer Chapter 6: Message Strategies Chapter 7: Print Media Chapter 8: Television, Radio, and Digital Video Chapter 9: Mobile, Text, and Telephone Chapter 10: Digital and Social Media Part 3: Serve and Adapt to Customers and Markets Chapter 11: Business-to-Business (B2B) Chapter 12: Fulfillment and Customer Service Chapter 13: Environmental, Ethical, and Legal Issues Chapter 14: International Direct Marketing Part 4: Applications, Examples, and Careers in Direct Marketing Comprehensive Cases Appendices
Includes and index.
Keywords: Direct marketing